Is automobile dependence in emerging cities an irresistible force? Perspectives from São Paulo, Taipei, Prague, Mumbai, Shanghai, Beijing, and Guangzhou - Kenworthy, Jeffrey (MDPI AG, 2017)
This paper analyses seven metropolitan regions that are all experiencing rapid motorisation and are perhaps appearing to capitulate to the automobile. Through 20 years of changes, evidenced in systematic data from the mid-1990s, a different perspective is found. None of the urban regions appear near to or even capable of becoming automobile cities. Physical limits are already being reached that make higher levels of private motorised mobility very problematic if transport systems are to remain functional and the cities livable. These limits appear already to be reversing the decline in non-motorised modes and creating an upturn in transit systems, especially urban rail. That these cities have been able to either hold their own, or somewhat increase their share of total motorised mobility by transit over a 20-year period, is some indication that they are 'hitting mobility walls' much sooner in the motorisation path than cities in North America and Australia, which grew up with and were designed around the spatial needs of cars. Like many cities in the developed world that have shown a decoupling of car use and total passenger mobility from GDP growth from 1995 to 2005, there is now evidence that this is happening in less wealthy cities. This is important because it assists global and local goals for reduced CO 2 from passenger transport, while allowing for economic progress. Such evidence suggests that automobile dependence is not an irresistible force in emerging economies. © 2017 by the author. Licensee MDPI, Basel, Switzerland.